The effect of contractual governance, relational governance, and supply chain technology on tacit knowledge - Aslam, Shazia; Kusumastuti, Mutiara Ratna (Journal of Management and Business Insight, 2025)
Purpose-Every business unit needs to implement tacit knowledge management to achieve its goals and win the competition. Many things can influence tacit knowledge. This study examines the effect of contractual governance, relational governance, and supply chain technology on tacit knowledge. Methodology-Using a quantitative approach and survey methods, this study collected data through questionnaires distributed to business actors in the textile and garment sector in Asia with a sample of 109 respondents. Data was analyzed using Structural Equation Modeling with Smart Partial Least Square software. Findings-The results showed that contractual and relational governance have a positive effect on tacit knowledge. Thus, supply chain technology also contributes to increasing tacit knowledge. Research Limitations-This study's limitations focus on the textile and garment business sector in Asia. Therefore, its results cannot be used as a reference for business actors in other sectors and regions. Novelty-This study provides a deeper understanding of the causal relationship between the variables studied. These findings are expected to offer practical recommendations for managers and practitioners in the field of supply chain management to improve the tacit knowledge of employees in the textile and garment industry.